2016
DOI: 10.1371/journal.pone.0150502
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diet and Exercise on Intestinal Integrity and Microbial Diversity in Mice

Abstract: BackgroundThe gut microbiota is now known to play an important role contributing to inflammatory-based chronic diseases. This study examined intestinal integrity/inflammation and the gut microbial communities in sedentary and exercising mice presented with a normal or high-fat diet.MethodsThirty-six, 6-week old C57BL/6NTac male mice were fed a normal or high-fat diet for 12-weeks and randomly assigned to exercise or sedentary groups. After 12 weeks animals were sacrificed and duodenum/ileum tissues were fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
183
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(201 citation statements)
references
References 58 publications
(70 reference statements)
8
183
2
8
Order By: Relevance
“…89,90 In adult rodents, exercise changes the gut microbial populations. [140][141][142][143] In turn, the composition of the gut microbiota may influence exercise performance of mice through anti-oxidant enzyme production. 144 In mice, exercise attenuates gut dysbiosis due to exposure to polychlorinated biphenyls.…”
Section: Discussionmentioning
confidence: 99%
“…89,90 In adult rodents, exercise changes the gut microbial populations. [140][141][142][143] In turn, the composition of the gut microbiota may influence exercise performance of mice through anti-oxidant enzyme production. 144 In mice, exercise attenuates gut dysbiosis due to exposure to polychlorinated biphenyls.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al [45] were among the first to report that physical exercise modifies intestinal microbiota composition. More recently, it has been shown that the effects of exercise on intestinal microbiota are partly independent from dietary changes [76]. Studies have suggested that moderate aerobic exercise may contribute to the growth of butyrate-producing bacteria [77].…”
Section: Physical Exercise and Colonic Luminal Content Characteristicsmentioning
confidence: 99%
“…High fat diet (HFD) induces metabolic and gut microbial changes [20][21][22] Although, exercise has shown to effectively reverse some of the detrimental metabolic effects of a HFD, the potential effect of exercise restoring the altered microbiota caused by HFD is still on debate. An 8-week, four-arm study analyzed the effect of HFD (60% of calories from fat) and exercise (1 h/ session, 6 d/week for 8 weeks at a speed of 7 m/min) on gut diversity.…”
Section: Exercise and Dietmentioning
confidence: 99%
“…The type of diet differed among the studies, the study performed by Kang et al [20] utilized a 60% fat-based diet, while the diets provided by both Denou & Campbell et al [21,22] consisted on a 45% fat-based diet. The studies that involved the diet with 45% of energy coming from fat were able to revert with exercise the effects in the microbiota caused by HFD, while the study utilizing a higher percentage of fat (60%) was not able to observe this restoration.…”
Section: Exercise and Dietmentioning
confidence: 99%
See 1 more Smart Citation